Repeated intratracheal instillation of zinc oxide nanoparticles induced pulmonary damage and a systemic inflammatory response in cynomolgus monkeys. Issue 5 (28th May 2021) - Park, Eun-Jung; Kim, Soo Nam; Yoon, Cheolho; Cho, Jae-Woo; Lee, Gwang-Hee; Kim, Dong-Wan; Park, Junhee; Choi, Inhee; Lee, Seung Hyeun; Song, Jeongah; Lim, Hyun-Ji; Kang, Min-Sung; et al.
Abstract: Recently, some researchers have demonstrated that inhaled zinc oxide nanoparticles (ZnONPs) induce an acute systemic inflammatory response in workers. Considering nonhuman primates are preferably considered an animal model for translational research due to their proven similarity with humans in terms of genetics and physiology, we intratracheally instilled ZnONPs to cynomolgus monkey for 14 days and identified the toxic mechanism and bioaccumulation. ZnONPs were rapidly ionized or aggregated in a simulated pulmonary fluid, and they attracted neutrophils to the lungs and increased the pulmonary level of inflammatory mediators. Additionally, thickened alveolar walls, fibrin clots, and hemorrhages were observed in the lungs of the monkeys instilled with the higher dose accompanied by cell debris in the alveolar ducts and alveoli. Dark-field microscopy images revealed translocation of ZnONPs into other tissues accompanied by an increase in the relative weight of livers to body weight. In addition, when instilled at the higher dose, the albumin/globulin ratio notably decreased compared to the control, whereas the C-reactive protein (CRP) level was significantly elevated. ZnONPs also clearly induced apoptotic cell death in a 24 h exposure to alveolar macrophages. Taken together, part of inhaled ZnONPs may be ionized in the lung, resulting in acute toxic effects, including cell death and tissue damage, and the rest may move to other tissues in the form of particles, causing a systemic inflammatory response. Based on the proven evidence among workers, we also suggest that the CRP level can be recommended as a biomarker for ZnONPs-induced adverse health effects.